Vegetative development of arabica coffee plants grafted onto robusta coffee, subjected to water replacement - Miranda, Wezer Lismar; Guimarães, Rubens José; Magalhães, Pedro Bueno; Colombo, Alberto; de Oliveira, Polyanna Mara (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the vegetative growth of Arabica coffee (Coffea arabica) plants grafted onto robusta coffee (C. canephora), subjected to different levels of water replacement. The experiment was carried out in Lavras, MG, Brazil, in a complete randomized block design, with a 2x2x5 factorial arrangement and four replicates. Evaluations were done for: two cultivars of C. arabica – Catuaí IAC-99 and Topázio MG-1190 –, two types of plants – ungrafted and grafted onto C. canephora 'Apoatã IAC-2258' –, and five levels of water replacement – the control without irrigation, and four crop coefficients with values of 0.2, 0.3, 0.4, and 0.5 from planting to 24 months, and of 0.4, 0.6, 0.8, and 1.0 from 24 to 29 months –. A fixed watering shift was used, with irrigations on Tuesdays and on Fridays. Plant height, and crown and stem diameters were evaluated. Grafted trees have lower growth compared to the ungrafted ones, during the establishment of the crop. The replacement of the root system of C. arabica by C. canephora does not alter the response of plants to irrigation.